DevOps and DNS : improving web application performance at the DNS layer - Still, Andy; Stanhope, Phil (O'Reilly Media, 2017)
For many developers, the Domain Name System (DNS) is simply a black box: something you rely on without knowing how it works. But when it comes to optimizing system performance and delivery, DNS is a very valuable tool indeed. If your company is ready to implement a DevOps culture, or is considering it, this practical report shows you how DNS can help you build the type of dynamic, fast-changing, and reliable system that DevOps demands. Author Andy Still, co-founder of Intechnica, a vendor-independent IT performance consultancy, shows you how to initiate a DNS-based DevOps approach in your company. Once you understand how DNS works, you'll learn how you can use it to streamline deployment pipelines, maximize availability, and mitigate performance degradations. Learn three key DevOps principles for delivering speed and reliability Use DNS to create flexible systems that support changing backend systems, and systems hosted in multiple locations Get advice for selecting a DNS provider, and for implementing an effective DevOps monitoring solution Manage DNS changes with a dynamic API so you can iterate and test the code in the same manner as application code Examine how Intechnica uses DNS to optimize deployments and minimize risk within its own DevOps culture.